Maxillary Canine Ectopia and Maxillary Canine-Premolar Transposition are Associated with Deviations in the Maxilla - Louise Miltenburg Caspersen; Ib Jarle Christensen; Inger Kjær (Dental Anthropology Association, 2010)
The purpose was to analyze the direction of the infraorbital canal and the palatal width in cases with maxillary ectopic canines, all oriented horizontally and erupted labially, and with canine transposition and to compare findings with normal values. Eight anthropological human skulls, four with these horizontally oriented ectopic canines and four with canine-premolar transposition comprised the study. A radiopaque marker was placed in the infraorbital canal and frontal and profile radiographs were taken of each skull. Cephalometric measurements evaluated the canal direction (IOt angle). Interorbital (IO) and palatal widths (PW) were measured directly on the skulls. A general linear model was used for statistical analysis. Maxillary canine ectopia: IOt ( x = 8.54; 95% CI of -3.95 and 21.04; P = 0.18) was larger, PW ( x = 3.37; 95% CI of 0.51 and 6.23; P = 0.022) was significantly smaller and IO ( x = 1.49; 95% CI of -2.62 and 5.61; P = 0.47) was also smaller. Maxillary canine-premolar transposition: IOt ( x = 17.27; 95% CI of 4.78 and 29.76; P = 0.008) and PW ( x = 3.34; 95% CI of 0.48 and 6.21; P = 0.023) were significantly smaller and IO ( x = 2.94; 95% CI of -1.17 and 7.06; P = 0.16) was smaller, but not significantly. Eruptional deviations in the maxillary canines-premolars are associated with maxillary deviations expressed as the direction of the infraorbital canal and the transpalatal width. Accordingly, dental and osseous deviations within the maxillary developmental field are interrelated.